2006
DOI: 10.1089/acm.2006.12.467
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults' Use of Complementary and Alternative Medicine for Mental Health: Findings from the 2002 National Health Interview Survey

Abstract: Older adults with self-reported anxiety or depression were more likely to use spiritual practices, relaxation techniques, and nonvitamin, nonmineral natural products than elders in good mental health. However, for the majority of older adults with self-reported anxiety or depression, CAM was used for purposes other than treating mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 26 publications
4
66
0
Order By: Relevance
“…The distinction between prevalence when spiritual and nonspiritual CAMs are included is important, as opinions and practices differ regarding whether spiritual practices should be considered as CAMs. For this reason, some studies exclude spiritual-based practices (American Association of Retired Persons, National Center for Complementary and Alternative Medicine, 2007;Matthews et al, 2007) whereas others report the results with and without spiritual-based practices (Barnes et al, 2002;Grzywacz et al, 2006). The analysis of the 2002 NHIS data for CAM use by US adults found that the most commonly used therapies were prayer for one's own health (43.0%), prayer by others for one's own health (24.4%), natural products (18.9%), deep breathing exercises (11.6%), participation in prayer group for one's own health (9.6%), meditation (7.6%), and chiropractic care (7.5%) (Barnes et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The distinction between prevalence when spiritual and nonspiritual CAMs are included is important, as opinions and practices differ regarding whether spiritual practices should be considered as CAMs. For this reason, some studies exclude spiritual-based practices (American Association of Retired Persons, National Center for Complementary and Alternative Medicine, 2007;Matthews et al, 2007) whereas others report the results with and without spiritual-based practices (Barnes et al, 2002;Grzywacz et al, 2006). The analysis of the 2002 NHIS data for CAM use by US adults found that the most commonly used therapies were prayer for one's own health (43.0%), prayer by others for one's own health (24.4%), natural products (18.9%), deep breathing exercises (11.6%), participation in prayer group for one's own health (9.6%), meditation (7.6%), and chiropractic care (7.5%) (Barnes et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the percentage of CAM usage varies between 35.3% and 86.3% [10][11][12][13][14][15] . In studies carried out on elderly individuals, the percentage of CAM usage varies between 27.7% and 88% 8,[16][17][18][19][20][21][22][23][24][25][26] . These methods have been preferred mostly by elderly who are well-educated 3,16,19 have a high socio-economical status 19,20 , are female 17,19,27,28 , and are younger elderly 16 .…”
Section: Araştirma Makalesi̇ / Research Articlementioning
confidence: 99%
“…Therefore, sleep quality improvement play an effective role in preventingrisk factors, raising immunity and improving socio-family performance (Schenck et al, 2003). Different medicine and non-medicine methodshave been used to improve the sleep quality of HPs (Grzywacz et al, 2005). Although medications help to improve some indices of sleep quality in these patients, various degrees of side effects heve been reported for these drugs and even in the study by Foley et al statedthat barbiturates leading to severe insomnia in hemodialysis patients is 50% of cases (Foley et al, 1995).…”
Section: Original Articlementioning
confidence: 99%